A Review of Calcium Pyrophosphate Deposition (CPPD) - R. Trebino, Christopher; R. Matcuk, George; B. Patel, Dakshesh; Christianakis, Stratos; J. Gottsegen, Christopher; M. Forrester, Deborah; A. White, Eric (Current Medical Imaging, 2016)
Calcium Pyrophosphate Deposition (CPPD) is an extremely common and treatable cause of acute and chronic arthritis. Its radiographic presentation should be recognized in order to suggest the diagnosis to the clinician. This review encompasses its broad variety of radiographic presentations as well as its appearance on CT, MRI, and ultrasound. A review of its nomenclature, epidemiology, pathophysiology, diagnosis, treatment, and clinical presentation is included as well.
Keywords: crystalline arthritis